Efektivitas Teknik Desensitisasi Sistematis dalam Konseling Kelompok untuk Mengurangi Kecemasan Akademik Siswa - Ainun Heiriyah; Aminah Aminah (Kuras Institute, 2022)
The research objectives are: 1. To determine the level of academic anxiety of students before being given group counseling services with systematic desensitization techniques at MTs Negeri 1 Banjarmasin; 2. To determine the level of academic anxiety of students before being given group counseling services with systematic desensitization techniques at MTs Negeri 1 Banjarmasin; and 3. To determine the effectiveness of group counseling with systematic desensitization techniques in reducing student academic anxiety at MTs Negeri 1 Banjarmasin. Furthermore, research results are published in online ISBN Proceedings or Nationally Accredited Scientific Journals. This study used an experimental method (non parametric). The reason the researcher used this experimental pattern was to see the effect of a treatment (Systematic Desensitization Technique Group Counseling) on ​​another variable (Academic Anxiety). Research design is all the processes needed in planning and carrying out research. This research is a quasi-experimental design, using a one group pre-test and post-test design. With the one group pre test and post test design method, this means that the sample is given a test before and after receiving certain treatment, so that the subject is subjected to two measurements. The subjects in this study were students who had a high academic anxiety background at MTs Negeri 1 Banjarmasin.